Kajian Profesionalisme dan Kode Etik Insinyur dalam Kualitas Pekerjaan Proyek Pembangunan Gedung X - Merisa Ayu Pramesti; Ridho Bayu Aji; Nufrizal Faried Hanafi; M. Sigit Darmawan; Budi Suswanto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study examines the application of engineering professionalism and ethical conduct in the construction of Building X, focusing on the quality of both substructure and superstructure works. The research was conducted through field observation, interviews with project stakeholders, and literature review, analyzed using a qualitative descriptive approach. Several issues were identified on site, including bore pile misalignment, waterlogging due to excess soil accumulation, poor concrete quality (honeycomb), and work delays caused by reinforcement order errors and subcontractor replacement. The assessment of professionalism and ethics refers to the 2021 Indonesian Code of Ethics for Engineers. The findings indicate that several aspects of professionalism, such as supervisory decisiveness, technical responsibility, and proactive communication, were applied appropriately. However, deviations were also observed, particularly in planning, quality control, and safety implementation. The study recommends improved coordination between supervisors and contractors, technical training for workers, and stronger enforcement of ethical compliance to enhance the overall quality of construction outcomes.